Outcomes in congenital and childhood complete atrioventricular block: A meta‐analysis. (27th January 2022) - Deshpande, Saurabh; Shenthar, Jayaprakash; Khanra, Dibbendhu; Isath, Ameesh; Banavalikar, Bharatraj; Reddy, Satish; Krishnappa, Darshan; Khan, Hassan; Kella, Danesh; Padmanabhan, Deepak
Abstract: Background: The long‐term outcomes of patients with congenital and childhood complete atrioventricular block (CCAVB/CAVB) after pacemaker implantation are unclear. Methods: We performed a meta‐analysis of all the studies of CCAVB. A systematic search of PubMed and CENTRAL databases from January 1, 1967 to January 31, 2020 was performed. The quality of studies included was critically appraised using the Newcastle–Ottawa scale, and outcome data were analyzed using the restricted maximum likelihood function. Results: Twenty‐nine studies were eligible for analysis, with a total of 1553 patients. The all‐cause‐mortality was 5.7% (95% confidence interval [CI]: 2.5%–9.9%), while pacing‐induced cardiomyopathy (PICM) was seen in 3.8% (95% CI: 1.2–7.2). Diagnosis at birth (effect size [ES] [95%CI]: −2.23 [−0.36 to −0.10]; p < .001), presence of congenital heart disease (ES [95%CI]: −0.67 [0.41–0.93]; p < .001), younger age at pacemaker implantation (ES [95%CI]: −0.01 [−0.02 to −0.001]; p = .02), and duration of pacing (ES [95%CI]: −0.03 [−0.05 to −0.003]; p = .03), were associated with an higher mortality on binominal logistic regression. None of the parameters were significant on multivariate analysis. Conclusion: Pooled proportional mortality in patients with CCAVB and CAVB is 5.7% with an infrequent incidence of PICM (3.8%) in the paced patients with AVB suggesting that pacing in these patients is an effective management strategy with a low incidence of long‐term side effects. Registry and randomized data can throw additional light regarding the natural history and appropriate management strategy in these patients.